Instrumentos de ordenación y gestión territorial y medioambiental. Marco normativo regulador de las actividades económicas en la Comunidad Valenciana - Ana María Blázquez Morilla (Cuadernos de Geografía de la Universitat de València)
This paper shows the new territorial and environmental normative framework, that has been introduced since 2004 in the Valencian Community. This recent legislative renewal has given rise to a series of new planning tools that are necessary to the establishment of any economic activity in our territory and that can be classified as concerning the territorial, urban and/or environmental spheres. In addition, the available public information sources, both cartographic and bibliographic, that allow an a priori assessment of the viability of a particular project, are also indicated.